Canine amniotic membrane transplantation for ocular surface reconstruction of created deep corneal ulcers in dogs - Simon Vongsakul (2018)
Canine amniotic membrane (AM) transplantation in conjunction with a third eyelid flap was used to promote healing of created deep corneal ulcers in 6 normal mongrel dogs. The healing was compared with the healing of created ulcers in the other eye of the same dog that were treated only with the third eyelid flap. A minimum of 60 days interval was allowed between the two treatment procedures in the 2 eyes of each dog. To simulate corneal ulcers found clinically, the surgical treatment was performed three days after the ulcer had been created. Cultures from preoperative conjunctival swabs revealed Staphylococcus spp., Streptococcus spp., and Enterococcus spp. The average time ± SE to complete corneal epithelialization in the eyes receiving the AM transplantation in conjunction with the third eyelid flap was 7.33±0.21 days which was significantly (p<0.05) shorter than the average time of 9.17±0.31 days observed in the eyes receiving only the third eyelid flap. Normal corneal transparency resumed in the eye receiving the AM transplantation and the third eyelid flap significantly (p<0.05) later than in the eye receiving only the third eyelid flap. Inflammation, neovascularization, and scar formation on the cornea, photophobia and impaired vision were not evident in any eyes at 8 weeks after either of the two surgical techniques. In conclusion, canine AM can promote the healing of created deep corneal ulcers in dogs.